MICROBIOLOGICAL ASSESSMENT OF THE EFFECTIVENESS OF THE TREATMENT OF PATIENTS WITH CONGENITAL CLEFT LIP AND PALATE BEFORE AND AFTER URANOPLASTY - Khatamov, Ulugbek Altibayevich (Educational Research in Universal Sciences, 2022)
This article presents an assessment of the effectiveness of the use of dental adhesive paste Solcoseryl and Hexoral aerosol, we studied the results of treatment in 54 sick children with congenital cleft palate.